2016
DOI: 10.1111/jcal.12132
|View full text |Cite
|
Sign up to set email alerts
|

Promoting contextual vocabulary learning through an adaptive computer‐assisted EFL reading system

Abstract: The study developed an adaptive computer‐assisted reading system and investigated its effect on promoting English as a foreign language learner‐readers' contextual vocabulary learning performance. Seventy Taiwanese college students were assigned to two reading groups. Participants in the customised reading group read online English texts, each of which was customised by the developed system to offer immediate and repeated meetings with previously encountered unknown words, while participants in the typical rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Consistent with the study's hypothesis, students who engaged in DC demonstrated statistically significant higher posttest scores on the main idea assessment than students in the control group. This finding was expected given that adaptive CAI programs has significantly improved a wide variety of literacy skills (Council III et al, 2016; Schechter et al, 2015; Shamir et al, 2017, 2018; Y. Wang, 2016) as well as that the DC program was grounded in a research‐based approach to main idea instruction (e.g., Boudah, 2014; Sulak & Güneş, 2017; Williams et al, 1983). This study's findings extends the success of adaptive CAI to main idea skills, which had not previously been tested.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with the study's hypothesis, students who engaged in DC demonstrated statistically significant higher posttest scores on the main idea assessment than students in the control group. This finding was expected given that adaptive CAI programs has significantly improved a wide variety of literacy skills (Council III et al, 2016; Schechter et al, 2015; Shamir et al, 2017, 2018; Y. Wang, 2016) as well as that the DC program was grounded in a research‐based approach to main idea instruction (e.g., Boudah, 2014; Sulak & Güneş, 2017; Williams et al, 1983). This study's findings extends the success of adaptive CAI to main idea skills, which had not previously been tested.…”
Section: Discussionmentioning
confidence: 94%
“…Specific to reading instruction, adaptive CAI has significantly improved elementary students' phonological awareness (Segers & Verhoeven, 2005; Shamir et al, 2018), phonics (Shamir et al, 2018), vocabulary and language development (Shamir et al, 2017; Y. Wang, 2016), word recognition (Cheung & Slavin, 2012; Shamir et al, 2017), and fluency (Council III et al, 2016; Shamir et al, 2017). A more limited body of research has shown that CAI has positive effects on reading comprehension (Schechter et al, 2015; Shamir et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the abundance of research on CALL might not necessarily look into teaching listening comprehension. Although the literature might provide some evidence regarding the role of computerized instruction in vocabulary learning (e.g., Wang, 2016) or grammar (Corbeil, 2007;Yusof & Saadon, 2012), studying computer software in teaching listening comprehension seems not to be sufficiently examined, particularly in the context of Iran and being integrated with group DA.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Early supporters of CALL programs (Gerard, 1967;Oliver, 1999; believed that these educational devices might pave the way for both teachers and learners to benefit from them in their language classroom, and create variety in the learning atmosphere, which probably leads to a more cooperative learning environment. Some of the expected benefits included self-paced instruction for students, which would result in faster learning, the availability of richer and more sophisticated materials, expert system-based instruction, and dynamic assessment (Corbeil, 2007;Wang, 2016;Zhao, 2003). The benefits for teachers were found to be the ease of modifying instructional materials and better time management, which allowed them to allocate more time to assist individual learners who required additional contact (Apperson, Laws, & Scepansky, 2006;Coleman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, los enfoques más estructurales de la enseñanza de lenguas extranjeras parecen alimentar el sueño de aproximaciones automáticas al aprendizaje, sea mediante aprendizaje adaptativo (Gavriushenko, Karilainen y Kankaanranta, 2015;Chukharev-Hudilainen y Klepikova, 2016;Forsyth et al, 2016;Wang, 2016) o incluso utilizando robots como tutores para el aprendizaje de idiomas (Kory, y Breazeal, 2014;Vogt, de Haas, de Jong, Baxter y Krahmer, 2017). Así, la tecnología se presenta como una aliada importante para la enseñanza de la pronunciación y la gramática, pasando por el léxico o los sistemas de corrección automática de la escritura, por citar solo algunas posibilidades.…”
unclassified